PENGARUH MODEL PEMBELAJARAN COLLABORATIVE TEAMWORK LEARNING (CTL) BERBANTUAN APLIKASI ASSEMBLR EDU TERHADAP PEMAHAMAN KONSEP IPAS PADA SISWA KELAS V SDN 63 SINGKAWANG - Effendi, Meri Utami; Emi Sulistri; Kamaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) find out how the science and science concept is understood by class V students at SDN 63 Singkawang; 2) to describe the differences before and after using the Collaborative Teamwork Learning (CTL) learning model assisted by the Assemblr Edu application in understanding science and science concepts for class V SDN 63 Singkawang; 3) to find out how much influence the use of the Collaborative Teamwork Learning (CTL) learning model assisted by the Assemblr Edu application has on class V students at SDN 63 Singkawang.  The research used was quasi-experimental research with a Pretest Posttest Control Group Design. The population in this study were fifth grade students at SDN 63 Singkawang. The research sample was taken by random sampling, selected by randomly selecting groups that used the CTL learning model and the learning model using PowerPoint and video.   The prerequisite test carried out was a normality test using the Chi-square formula, a variance homogeneity test was carried out to see the similarity of the variants in the two groups and the effect size. The results of the research showed that students' understanding of the science and science concept was categorized as sufficient and high, there was a difference before and after using the Collaborative Teamwork Learning (CTL) learning model assisted by the Assemblr Edu application in the understanding of the science and science concept in class V students at SDN 63 Singkawang of 0.012 < 0, 05, and the magnitude of the influence of using Collaborative Teamwork Learning (CTL) learning assisted by the Assemblr Edu application on fifth grade elementary school students is categorized as sufficient.